No association between perceived exertion and session duration with hamstring injury occurrence in professional football - Lolli, L.; Bahr, R.; Weston, M.; Whiteley, R.; Tabben, M.; Bonanno. D.; Gregson, W.; Chamari, K.; Di Salvo, V.; van Dyk, N. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Training and competition loads have emerged as modifiable composite risk factors of non-contact injury. Hamstring strains are the most common injuries in football with substantial burden on the individual player and club. Nevertheless, robust evidence of a consistent load-hamstring injury relationship in professional football is lacking. Using available data from the Qatar Stars League over three competitive seasons, this study investigated the separate and combined effects of perceived exertion and session duration on hamstring injury occurrence in a sample of 30 outfield football players. Load variables were calculated into 7-day, 14-day, 21-day, 28-day periods of data, and week-to-week changes for average ratings of perceived exertion (RPE; au) score and session-RPE (s-RPE; session-duration x score), plus the cumulative training and match minutes and s-RPE, respectively. Conditional logistic regression models estimated load-injury relationships per 2-within-subject standard deviation increments in each candidate variable. Associations were declared practically important based on the location of the confidence interval in relation to thresholds of 0.90 and 1.11 defining small beneficial and harmful effects, respectively. The uncertainty for the corrected odds ratios show that typically high within-subject increments in each candidate variable were not practically important for training- and match-related hamstring injury (95% confidence intervals range: 0.85 to 1.16). We found limited exploratory evidence regarding the value of perceived exertion and session duration as etiological factors of hamstring injury in Middle-East professional football. Monitoring remains valuable to inform player load management strategies, but our exploratory findings suggest its role for type-specific injury risk determination appears empirically unsupported.